Italijani in Madžari v Sloveniji v perspektivi etničnih študij - participacija v politiki in pri urejanju javnih zadev - Jesih, Boris (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The contribution addresses the issue of the participation of national minorities and the ways in which this participation can be optimally regulated. After a brief introductory discussion of the advantages and disadvantages of the available models of integration and autonomy, the author turns to the political organisation of the Italian and the Hungarian minorities in Slovenia, in three consecutive periods: before 1974 when the constitution of the SR of Slovenia was adopted, from 1974 and 1991, and after its Slovenia's independence in 1991. The author concludes that the political participation of the constitutionally and legally recognized minorities has always been guaranteed on the declarative level and progressively also on the normative level. The normative development achieved before 1991 directly influenced the formulation of the solutions that were applied after the independence and thereby assured certain continuity of contents. The legal regulation of the political participation of the two autochtonous national communities is exemplary, although there have always been some discordances between the normative regulation and the actual situation. Despite the professional interest in the issue of political participation of the two authochotous national minorities, the transfer of the research results into direct political action and development of better political solutions has beenvirtually non-existent.
Keywords: Slovenia; Slovenija; narodne manjšine; narodnostno vprašanje; Italijani; Madžari; politična participacija; javna uprava